SERVICE TYPOLOGIES: A STATE OF THE ART SURVEY - Cook, David P.; Goh, Chon‐Huat; Chung, Chen H. (Production and Operations Management, 1999)
Services comprise an ever‐expanding source of employment in the world's economies and are of significant interest to both academicians and practitioners. In this study, historical perspectives from which to view service typologies are provided and four decades of service typologies are chronicled. The interest in services demonstrated by academicians is tracked over time as are the purposes for which typologies have been developed. A unified schematic representation of services is developed in which the common themes underlying service typology development are identified from both a macro and micro level. Based on this study, areas for future research are identified.